2014
DOI: 10.1097/sla.0000000000000348
|View full text |Cite
|
Sign up to set email alerts
|

Regional Lymphadenectomy Is Indicated in the Surgical Treatment of Pancreatic Neuroendocrine Tumors (PNETs)

Abstract: Objective To explore the prognostic importance and preoperative predictors of lymph node metastasis in an effort to guide surgical decision making in patients with pancreatic neuroendocrine tumors (PNETs). Background PNETs are uncommon, and the natural history of the disease is not well described. As a result, there remains controversy regarding the optimal management of regional lymph nodes during resection of the primary tumor. Methods A retrospective review of a prospectively maintained database of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
140
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(164 citation statements)
references
References 35 publications
14
140
2
8
Order By: Relevance
“…p-NEC exhibits a poor prognosis (24) and previous evidence has demonstrated the decreased survival rate of patients with p-NEC (25,26). Furthermore, increased lymph node metastasis in p-NEC was observed in the present study.…”
Section: Discussionsupporting
confidence: 68%
“…p-NEC exhibits a poor prognosis (24) and previous evidence has demonstrated the decreased survival rate of patients with p-NEC (25,26). Furthermore, increased lymph node metastasis in p-NEC was observed in the present study.…”
Section: Discussionsupporting
confidence: 68%
“…Two recent studies using the SEER tumor registry concluded that lymph node dissection is necessary, to predict the outcome of the patient. Furthermore high grade tumors and large tumors predicted nodal positivity and decreased disease specific survival [19][20]. Our findings support this data: patients with positive lymph nodes had a significantly higher risk for metastases or recurrences.…”
supporting
confidence: 81%
“…Tumour grade was previously considered as a supplementary tool to predict presence of regional lymph node metastases [43,44,45]. In this study, G2/G3 vs. G1 grade showed at best moderate ability to detect pN1 stage.…”
Section: Ki67 LI Is Imperfect Predictor Of Regional Lymph Node Metastmentioning
confidence: 68%
“…This gives lower morbidity but is associated with a risk of metastasis in regional lymph nodes which are not resected (as discussed in [43,44,45]). Risk of LN metastasis in G2 tumours is higher than in G1 [43,44,45], but LN metastasis is not rare in G1 tumours (7.5% [45] -23.1% [43]). …”
Section: Ki67 LI As a Risk Factor Of Regional Lymph Node Metastasismentioning
confidence: 99%